Monetary policy in India - Kumar, B. (Birendra) 1935- (Delhi Amar Prakashan, 1983)
Study primarily covers the period 1950-51 to 1973-74.
Revision of the author's thesis (D. Litt.--Ranchi University, 1981)
Keywords: Monetary policy -- India; Monetary policy